Islamic Defenders Front Community Organizations and the Legal Effects of Joint Ministerial Decrees and Institutions - Fadloli; Shohib Muslim; Abdul Chalim; Khrisna Hadiwinata; Nandaru Ramadhan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to ascertain the legal ramifications of joint ministerial directives and institutions with regard to the continued existence of the Islamic Defenders Front Community Organization. The normative juridical strategy used in this research is one that looks at theories, conceptions, legal principles, rules, and regulations that are relevant to the topic at hand. The government is attempting to outlaw FPI-related activities through the Joint Decree of Ministers and Institutions, not disbanding community organizations affiliated with the FPI. The government's decision to impose the ban is justified by the fact that FPI has not been registered as a community organization since 2019.The legal significance of the joint decree of the Minister and the Institution for the continuation of the community programs of the Islamic Defenders Front is explained in this paper. This study examines the legitimacy of a decree with the Minister and Institutions and the Islamic Buyer's Front as a community organization